Cost-Minimization Analysis of Sacubitril/Valsartan and Ramipril in Hospitalized Heart Failure Patients at RSUP Dr. Kariadi Semarang - Hadianti Deliana Rifqi; Maria Caecilia Nanny Setiawati; Fef Rukminingsih Fef Rukminingsih; Yuliana Setyarini (Jurnal Riset Kefarmasian Indonesia, 2026)
Heart failure represents a major public health challenge in Indonesia, characterized by high hospitalization rates and substantial healthcare costs. This study compared the economic efficiency of sacubitril-valsartan and ramipril in hospitalized heart failure patients through cost-minimization analysis. This study was conducted in a retrospective cross-sectional at RSUP Dr. Kariadi Semarang from January to December 2024, Analyzed 98 patients who received sacubitril-valsartan or ramipril in conjunction with beta-blockers and mineralocorticoid receptor antagonists, and did not undergo minor or major surgery during hospitalization, with data sourced from medical records, hospital systems, pharmacy, and finance departments. Patient baseline characteristics showed no significant differences in sex, occupation, or length of stay, though sacubitril-valsartan patients had more comorbidities and different insurance and education profiles. Length of stay averaged 5.78 days for ramipril and 6.18 days for sacubitril-valsartan, with no statistical difference. Total hospital costs reached 12,379,257 IDR per patient for ramipril versus 12,174,742 IDR for sacubitril-valsartan. Sacubitril-valsartan proves economically comparable to ramipril, offering a slight cost advantage from the payer perspective under equivalent clinical effectiveness. These findings support its integration into Indonesian heart failure protocols to optimize resource use amid budget constraints.